Modelling heterogeneous degradation of polymeric devices due to short chain diffusion - Pan, J.; Chen, X.
A diffusion equation for short chains is coupled with the rate equation for chain scission presented in the previous chapters. This leads to a complete set of governing equations for the degradation of three-dimensional devices. The model is able to interpret the size effect observed in degradation experiments. Degradation maps are presented which graphically illustrate different behaviours of device degradation for different polymers and device dimensions. This chapter focuses on simple devices such as plates and pins for which the diffusion is one-dimensional. Application to the design of three-dimensional devices is the topic of Chapter 7. © 2015 Elsevier Ltd. All rights reserved.
Keywords: BIODEGRADABLE IMPLANTS; BIODEGRADATION; DEGRADATION MAP; MODELLING; REACTION-DIFFUSION EQUATION; SIZE EFFECT